Implementasi Komunikasi Persuasif Dalam Produksi Video “dibalik Dapur Kebabfactory.id” Sebagai Director Of Photography - Pratama, Reza Ilhami; Abdullah, Nisa Nurmauliddina (eProceedings of Management, 2024)
The study titled "THE ROLE OF DIRECTOR OF PHOTOGRAPHY IN THE PRODUCTION OF KEBABFACTORY.ID COMPANY PROFILE VIDEO" explores the role of the Director of Photography (DoP) in creating acompany profile video for Kebab Factory.ID, a company in the F&B sector specializing in kebabs. The backgroundof this research is based on the rapid development of information and communication technology, which influenceshow information is disseminated, including through digital media and video. In this context, a company profile videobecomes a crucial tool for building a company's image and fostering collaborations. The research methodologyinvolves the stages of video production, divided into three main phases: pre-production, production, and postproduction. The pre-production stage includes research and planning the video's concept and story, while theproduction stage involves filming at various locations. The post-production stage focuses on editing and refining thevideo. The results show that the application of cinematography theory and uses and gratifications theory plays asignificant role in creating appealing and informative visuals. The 5C concept in cinematography (camera angle,continuity, composition, close up, and color) is used to create an inspiring and effective video in conveying themessage. In conclusion, the Kebab Factory.ID company profile video successfully introduces the company to thepublic, showcases its history and flagship products, and builds an emotional connection with the audience. This studyemphasizes the importance of the DoP's role in ensuring visual and audio quality aligns with the initial concept andthe relevance of video as an effective communication tool in the digital era. Keywords- director of photography, company profile, cinematography, digital media, information technology.